Application of Smoothed Particle Hydrodynamics Method for Tsunami Force Modeling on Building with Openings - Anggita, Putra; Triatmadja, Radianta; Yuwono, Nur (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Smoothed Particle Hydrodynamics (SPH) serves as a numerical technique extensively employed for simulating free surface flow. The computational intricacy of the SPH method arises from the numerous computations of a particle's properties, derived from interactions with surrounding particles. To address this complexity, experts developed DualSPHysics. This study employs the SPH method, specifically the DualSPHysics application, for tsunami modeling. To accurately represent tsunami characteristics, precise numerical parameters are essential for numerical modeling. This research provides valuable insights into optimizing numerical parameters for accurate SPH simulations. Therefore, the research aims to identify the exact values of crucial parameters in DualSPHysics model. Validation of numerical calculations involves comparing the tsunami forces, as simulated by DualSPHysics, with secondary data obtained from physical experiments results. The findings highlight the significance of particle size (dp) as a crucial numerical parameter in DualSPHysics modeling. A smaller particle size contributes to model's accuracy. The determination of the particle size must account for model's shortest characteristic (s). According to simulations those have been carried out, it is recommended to set the maximum limit value of dp/s at 1/3.67 to achieve precise calculation. Furthermore, the DualSPHysics simulation demonstrates a reduction in force due to the opening configuration (n).